Synthesis and characterization of Mn–Co–Ni–O ceramic nanoparticles by reverse microemulsion method. Issue 2 (March 2015) - Chen, Long; Kong, Wenwen; Yao, Jincheng; Zhang, Huimin; Gao, Bo; Li, Yonglei; Bu, Haijun; Chang, Aimin; Jiang, Chunping
Abstract: Mn–Co–Ni–O ultrafine ceramic nanoparticles are successfully synthesized by the reverse microemulsion method in a triton X-100/ n -hexanol/cyclohexane system. The thermal decomposition process, crystallinity and crystal structure of Mn–Co–Ni–O powders are investigated and characterized by thermogravimetric-differential scanning calorimetry (TG/DSC), Fourier Transform Infrared (FT-IR), X-ray powders diffraction (XRD) and High Resolution Transmission Electron Microscope (HRTEM), respectively. The TGA/DSC, FT-IR and XRD results show that the reverse microemulsion method can effectively reduce the calcination temperature to 600 °C for synthesizing cubic spinel phase Mn–Co–Ni–O ceramic particles. Furthermore, the XRD and HRTEM images reveal that the particles are highly crystalline and have a narrow and uniform particle size distribution. These findings indicate that Mn–Co–Ni–O nanoparticles prepared via reverse microemulsion process meet demands for obtaining better microstructure and performance of Mn–Co–Ni–O materials.